Componential Analysis of Meaning of the Word “Melihat” In Javanese and English Language - Mamik Nugraheni (Register Journal, 2009)
It is a qualitative descriptive study that attempts to depict the componential meaning of the word ‘melihat’ or ‘to see’ in Javanese and English and the element of context that may influence the word choice in both languages. By using documentation as method of data collection, it is found that there are many different words having the same meaning to say ‘melihat’ in both languages while those words means that anyone doing activities of ‘melihat’. In addition, the aspects of intensity, target, distance, and connotative features influence the word choice in either Javanese or English. Keywords: Componential Meaning; Melihat; Javanese; English